Creative Criticism An Anthology and Guide - Benson, Stephen (Edinburgh University Press, 2022)
A guide to the creative possibilities of critical writing, with sample texts from a range of writer/criticsGBS_insertPreviewButtonPopup(['ISBN: 9780748674336','ISBN: 9780748674343','ISBN: 9780748674329']);Including pieces by creative critics as varied as Anne Carson, Jacques Derrida, Geoff Dyer, Hélène Cixous, Ali Smith, and John Cage, this anthology and guide celebrates the formal and intellectual inventiveness of works which also demonstrate a deep fidelity to the writing or art they address. The Anthology is of interest to all students, teachers and critics of literature and creative writing, and especially those students who are required to write critical essays. All 14 texts included respond innovatively to the question: How do we write criticism? As examples of academic critical writing they are all sympathetic to works whose aim is to change the ways in which we see and describe our world.